GENEALOGICAL NARRATIVES AND AFFECTIVE ETHNOPHOTOGRAPHY IN THE PRODUCTION OF THE VITAL ARCHIVE OF OUR ANTI-EXTRACTIVE FEMINIST STRUGGLES - Gamboa, Marianela (Instituto Regional de Planeamiento y Hábitat (RPHA), Unidad Doble dependencia CONICET y UNSJ, 2023)
This work reflects upon anti-extractivist feminism, especially about its emer- gence and divergences with hegemonic and ecofeminist feminism, put for- ward by scholars from Abya Yala in a context of profound neo-extractivist advances. To this end, the epistemic-methodological power of producing anti- extractivist feminist genealogical narratives is put into consideration by shar- ing, from affective ethnophotography, a collective experience of defense and care of the commons: the Walk of the Guardians of the Hill and the Water, held in April of 2021 in the province of Catamarca (Argentina), understanding this political fact and its record as part of the multi-situated vital archive of the struggles of resistance against the Agua Rica-Alumbrera mining project and the violence of the state-business (hetero)patriarchal-colonial-capitalist front which perpetuates the long process of dispossession and alterization of our bodies-territories.